2009
DOI: 10.1002/tee.20385
|View full text |Cite
|
Sign up to set email alerts
|

A nonlinear model to rank association rules based on semantic similarity and genetic network programing

Abstract: Many methods have been studied for mining association rules efficiently. However, because these methods usually generate a large number of rules, it is still a heavy burden for the users to find the most interesting ones. In this paper, we propose a novel method for finding what the user is interested in by assigning several keywords, like searching documents on the Web using search engines. By considering both the semantic similarity between the rules and keywords, and the statistical information like support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…As mentioned above, the conventional GNP‐based class association rule mining is one of the widely accepted state‐of‐art technologies in the field of class association rule mining [15–19,31–35]. There are other class association mining approaches, but they lack feasibility and practicality in the case of our study.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above, the conventional GNP‐based class association rule mining is one of the widely accepted state‐of‐art technologies in the field of class association rule mining [15–19,31–35]. There are other class association mining approaches, but they lack feasibility and practicality in the case of our study.…”
Section: Resultsmentioning
confidence: 99%
“…Each local predictability value is actually the prediction performance of that rule in one local test set which is generated by k-fold cross-validation. In 2008, Yang et al [40] suggested a personalized association rule ranking method based on Genetic Network Programming (GNP). The method learns a ranking measure which is a linear combination of semantic similarity and other well-known interestingness measures, includes support, confidence, lift and chi-squared.…”
Section: Related Workmentioning
confidence: 99%
“…The RuleRank model [3] is evolved by Genetic Network Programming. GNP is an extension of GP, which uses directed graphs as genes for evolutionary computation [4] [5], and evolves the graph structure with a predetermined number of nodes, so that it could be quite compact and efficient and never cause the bloat.…”
Section: Rulerank Modelmentioning
confidence: 99%
“…There has been some studies about combining different measures for ranking rules by evolutionary methods [3]. In this paper, we extend the method for associative classification.…”
Section: Introductionmentioning
confidence: 98%